REBRANDING NILAI-NILAI BATIK JEMBER SEBAGAI UPAYA EDUKASI DAN MEWUJUDKAN SEGMENTASI PRODUK LOKAL JEMBER - Elok Rosyidah (UPT Penerbitan Universitas Jember)
Batik is the result of a craft that has high artistic value and has become part of Indonesian culture, especially Javanese culture since long. Batik has spread to remote corners of the country in Indonesia not only in cities like Yogyakarta, Solo and Pekalongan famous for its batik industry centers. At the eastern end of the island of Java that is in the city of Jember existing batik industrial center. Shaping the image of batik Jember values is not enough to make and sell batik to the public, but there needs to education and socialization of batik itself. Characteristic of batik Jember developed in the society contains values then in actulization by batik artist that people easily remember and accept that characteristic is not out of cultures in Jember. Segmentation batik Jember also worth noting, remember people Jember identical with the Pandalungan which have diverse characteristics, lifestyle and behaviour, so that producers need to think about and define marketing strategies, even an active role of local goverments is crucial to encourage batik Jember be one icon in Jember and is recognized and is known nationally and internationally.